Impact of Dividend Announcement on Share Price: An Evaluation Study - Selvam, M.; Babu, M.; Indhumathi, G.; Kogila, N. (Indian Journal of Finance, 2010)
An efficient and integrated financial market is an important infrastructure that facilitates savings, investments and consequent economic growth. The financial markets include money market and capital market. Capital market is the market for trading long-term securities whereas; money market is for short-term securities. It is a universally accepted fact that the financial system and the capital market in particular act as the barometer of the health of an economy. Free and efficient capital markets ensure that the resources are allocated wisely and faster. The event study is an important research tool in economics and finance. The goal of an event study is to measure the effects of an economic event on the value of firms. Event study methods exploit the fact that given rationality in the marketplace, the effects of an event will be reflected immediately in security prices. Thus, the impact can be measured by examining security prices surrounding the event. There are various types of events like Mergers&Acquisitions, Quarterly Earnings, Dividend Issue, Bonus Issue, Stock Split, Buyback of Share, etc. that has a reaction over the prices of securities in the capital market. Bonus shares are free shares of stock given to current shareholders, based upon the number of shares that a shareholder owns. While this stock action increases the number of shares owned, it does not increase the total value. This is due to the fact that since the total number of shares increases, the ratio of number of shares held to the number of shares outstanding remains constant.